'The very heart of the Gospel': penal substitution in British Pentecostalism. Issue 2 (3rd July 2022) - Black, Jonathan
ABSTRACT: Increasingly, questions have been raised as to whether penal substitution is a properly Pentecostal account of the atonement, with suggestions that it is either incompatible with Pentecostal theological commitments or that it is an imported evangelical doctrine which is alien to a Pentecostal identity and thus could be jettisoned without detriment. However, many Pentecostal denominations around the world are committed to penal substitutionary models of the atonement in their confessional statements, preaching, hymnody, and prayers. This article takes up the discussion from a British Pentecostal perspective, examining the place of penal substitutionary accounts of the atonement and the centrality of the cross in the earliest days of the Pentecostal revival in the UK and the early years of the Apostolic Church and the Elim Foursquare Gospel Alliance, two of the UK's oldest Pentecostal denominations. This will demonstrate that penal substitution is foundational to the British Pentecostal understanding of the atonement.